2015
DOI: 10.1073/pnas.1507625112
|View full text |Cite
|
Sign up to set email alerts
|

CD300f associates with IL-4 receptor α and amplifies IL-4–induced immune cell responses

Abstract: IL-4 receptor (R) α, the common receptor chain for IL-4 and IL-13, is a critical component in IL-4-and IL-13-mediated signaling and subsequent effector functions such as those observed in type 2 inflammatory responses. Nonetheless, the existence of intrinsic pathways capable of amplifying IL-4Rα-induced responses remains unknown. In this study, we identified the myeloid-associated Ig receptor CD300f as an IL-4-induced molecule in macrophages. Subsequent analyses demonstrated that CD300f was colocalized and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 31 publications
3
70
0
Order By: Relevance
“…In addition to the data reported here showing CD300b regulation of TLR4 signaling, we have recently shown that CD300f associates with and regulates IL-4 receptor α-mediated responses by augmenting IL-4 and IL-13-induced signaling (Moshkovits et al, 2015). Other CD300 family members have been shown to modulate LPS-induced responses, although not through the direct recognition of LPS.…”
Section: Discussionsupporting
confidence: 64%
“…In addition to the data reported here showing CD300b regulation of TLR4 signaling, we have recently shown that CD300f associates with and regulates IL-4 receptor α-mediated responses by augmenting IL-4 and IL-13-induced signaling (Moshkovits et al, 2015). Other CD300 family members have been shown to modulate LPS-induced responses, although not through the direct recognition of LPS.…”
Section: Discussionsupporting
confidence: 64%
“…We have recently shown that CD300f is physically associated with IL-4Rα and that it is necessary for IL-4-induced activation of multiple cells including macrophages and eosinophils. In fact, IL-4 stimulated Cd300f −/− macrophages display decreased activation of STAT6 and subsequently decreased induction of hallmark alternatively activated markers such as Relm-α and arginase1 44 . Thus, on one hand Cd300f −/− mice display elevated eosinophilia which secrete increased levels of IL-4 and on the other hand, Cd300f −/− macrophages may be less responsive to IL-4, which may cause them to promote obesity and glucose intolerance.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Moshkovits et al did not detect CD300f expression on colonic macrophages or mast cells, and they failed to examine CD300f expression on DCs (34), whereas we detect CD300f expression on macrophages, DCs, neutrophils, and mast cells in colonic lamina propria (Supplemental Figure 11); similarly, Matsukawa et al (20) readily detected CD300f on the surface of colonic mast cells, macrophages, and eosinophils. The lack of detection of CD300f on lamina propria macrophages by Moshkovits and colleagues is surprising, as, in general, macrophages could be considered a hallmark of CD300f expression (18,(35)(36)(37). CD300f expression has been shown to be regulated by various cytokines (38,39), which could depend on exposure to environmental factors and/ or different microbiota communities present in the animal facilities.…”
Section: Cd300fmentioning
confidence: 99%
“…The lack of detection of CD300f on lamina propria macrophages by Moshkovits and colleagues is surprising, as, in general, macrophages could be considered a hallmark of CD300f expression (18,(35)(36)(37). CD300f expression has been shown to be regulated by various cytokines (38,39), which could depend on exposure to environmental factors and/ or different microbiota communities present in the animal facilities. Although cohousing revealed that the increased sensitivity of colitis in CD300f-deficient mice was not due to differences in the gut microbiota in our experimental settings, we cannot exclude the possibility of substantial differences in the composition of gut microbiota or other environmental factors across the different animal facilities used in all 3 studies.…”
Section: Cd300fmentioning
confidence: 99%